Maternal and umbilical cord blood polymorphonuclear leukocytes showed moderate oxidative burst at phagocytosis of Gardnerella vaginalis - Anushia Swaminathan (BMC, 2021)
Abstract Objective Pregnant women with bacterial vaginosis due to Gardnerella vaginalis (GV) infection presents with a wide-ranging disease symptomatology. We speculate this may be due to interaction that varies between host immune response and the pathogen. We studied the oxidative burst in polymorphonuclear leukocytes (PMNL)s from maternal blood (MB) and cord blood (CB) upon phagocytosis of GV and compared against E. coli and Group B Streptococcus (GBS). Results The PHAGOBURST™ assay detects fluorescence from oxidized dihydrorhodamine during oxidative burst. The average percentage of PMNL showing oxidative burst was almost two-fold greater with GBS (99.5%) and E. coli (98.2%) than GV (56.9%) (p  < 0.01) in MB, but a similar proportion of PMNL with burst activity was seen in CB (84.7%). The mean fluorescence intensity (MFI) of oxidative burst in MB PMNL with GV was lower compared to E. coli but comparable to GBS. The MFI of CB PMNL (1580 ± 245.8) was significantly higher than MB PMNL (1198 ± 262.1) with GV, p  = 0.031. The live-cell imaging showed neutrophil oxidative burst upon phagocytosis of GV produces hypochlorous acid (HOCl). Overall, the HOCL-mediated microbicidal activity against GV is more variable and less robust than E. coli and GBS, especially in maternal than CB PMNL.